Asylum as a Human Right in International Law: Theory and Practice in Pakistan - Naqeeb Ullah Tareen (Journal of Religion and Society, 2025)
The ability to apply for asylum is a key element of international humanitarian law. It provides support and protects to the individuals who are trying to escape from threats they see in their home countries. This article probs into the foundation of asylum as a human right under the international law. It also emphasizes the issues and challenges faced by asylum seekers and refugees in a country like Pakistan which is not a signatory state to the 1951 Refugee Convention. This article discusses the asylum law refugee policy and the challenges faced by the asylum seekers in Pakistan. It critically analyzes the huge gap between international legal policy makers and domestic authenticities. This article recommends the parameters of asylum practice in Pakistan into the position of international human rights of asylum seekers. This article will examine the right to asylum as a human right endorsed in international law where Pakistan is lacking its practical enforcement. Pakistan being not a signatory of the 1951 Refugee Convention and its 1967 Protocol has created complications in the implementation of asylum laws in Pakistan, but Pakistan has hosted a huge number of refugees for more than four and half decades. The legal framework related to the asylum and for dealing with asylum seekers of Pakistan is very primal. This article focuses on the legal and policy framework of Pakistan, examines the situation of asylum seekers in Pakistan and recommends to modify the legal framework and asylum policy for better protection of refugees and asylum seekers. Keywords: Asylum, Human Right, International Law, Refugees, Policy Framework